Effects of dietary and physical activity interventions on generic and cancer-specific health-related quality of life, anxiety, and depression in colorectal cancer survivors: a randomized controlled trial - Ho, Mandy; Ho, Judy W. C.; Fong, Daniel Y. T.; Lee, C. F.; Macfarlane, Duncan J.; Cerin, Ester; Lee, Antoinette M.; Leung, Sharron; Chan, Wynnie Y. Y.; Leung, Ivy P. F.; Lam, Sharon H. S.; Chu, Natural; et al. (Journal of cancer survivorship, 2020)
Purpose To assess the effects of dietary and physical activity (PA) interventions on generic and cancer-specific quality of life (QoL), anxiety, and depression levels among adult Chinese colorectal cancer (CRC) survivors. Methods Two-hundred twenty-three adult CRC survivors within 1 year of completion of primary cancer treatment were randomized to receive dietary, PA or combined intervention, or usual care for a 12 monthduration, under a 2 (diet vs usual care) × 2 (PA vs usual care) factorial design. Generic and cancer-specific QoL was assessed using a Chinese version 12-Item Short Form Health Survey (SF-12) and the Functional Assessment of Cancer Therapy-Colorectal (FACT-C) scale, respectively. Anxiety and depression was assessed using the Hospital Anxiety and Depression Scale at baseline, 6, 12, 18, and 24 months. Linear mixed models were used for examining the intervention effects. Results Participants receiving dietary intervention experienced a significant improvement in the generic measure of QoL (SF-6D utility scores, mean difference 0.042, 95%CI 0.03 to 0.081) at 12 months, the cancer-specific QoL scores (mean difference 3.09, 95%CI 0.13 to 6.04), and levels of depression ( P = 0.015) at both 12 and 24 months follow-up. Participants receiving PA intervention only demonstrated a significant improvement in SF-6D utility index (mean difference 0.039, 95%CI 0.002 to 0.077) and physical functioning (mean difference 2.85, 95%CI 1.00 to 4.70) at 6 months. Conclusions Dietary intervention improved the generic and cancer-specific QoL and depression in CRC survivors. Trial registration The study was prospectively registered on 17 October 2012 at ClinicalTrials.gov (NCT01708824). Implications for Cancer Survivors CRC survivors can benefit from dietary interventions in alleviating depression and improving overall health-related QoL.